Improving Control Theory Education Through Face-to-Face Implementation of a Mobile Robotics Methodology - Pastrana, M. A.; Sánchez, William Humberto Cuéllar; Mendoza-Peñaloza, Jose; Santana, M. S.; Muñoz, Daniel M. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
Advances in information and communication technologies have significantly transformed engineering education. Virtual laboratories are increasingly adopted to enhance student interaction with control system simulations. The improved visualization and interaction capabilities of modern computers offer a more organic way to teach theoretical foundations. This paper describes the implementation of a methodology for teaching control theory that until now was entirely online in a face-to-face environment at the University of the Federal District in Brasilia, Brazil. This methodology utilizes virtual laboratories with CoppeliaSim, MATLAB, and the EVA mobile robot to teach control theory focused on single-input, single-output (SISO) systems for mobile robot tracking and obstacle avoidance applications. The results of the face-to-face implementation are compared to those of the fully online methodology, revealing that in-person teaching significantly enhances the quality of instruction.